Project-based learning for teaching writing skill at tourism major in vocational school - Elin Yulianty; Miftah Al Farhan (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
Tourism major in vocational school learns English for doing promotion to attract foreign tourists. One of promotion media often used is brochure. It is learned by tourism students in the classroom through writing skill learning that can be taught using project-based learning method. Thus, the present study aims to explore the application of project-based learning to teach writing skill at tourism major and investigate students' perceptions towards it. A case study method was used in this study to gain the research data. Through in-depth interview and direct observation, one English teacher and two students classified as the high-level and the low-level students were involved as research participants. The results of this study find that the learning objective of English lesson for one semester is to learn how to write an essay for tourist promotion brochure. To help students develop their ideas, the teacher organized a tour with all students to one of local attractions. In the classroom, the brochure project is assigned to individual students with the assistance of the teacher to help them write the essay more effectively. In the end, the brochure must be presented for evaluation and further improvement. In addition, the students confirmed that they enjoy the learning process because the teacher often helps when they are having difficulties in writing the essay for brochure.